Cost-effectiveness of chikungunya vaccination with the live attenuated vaccine in U.S. territories - Kelly Kilburn; Martin I. Meltzer; Seonghye Jeon; Bishwa B. Adhikari; Nicole Lindsey; Susan L. Hills; J. Erin Staples (npj Vaccines)
Abstract A live attenuated chikungunya vaccine, IXCHIQ, was approved in the United States in 2023 for use in adults. We assessed the cost-effectiveness of two different vaccination strategies, routine and outbreak vaccination, for persons aged ≥18 years living in U.S. territories with previous transmission. We included the entire population of impacted U.S. territories and assumed one chikungunya outbreak occurring during a 30-year time horizon. We estimated that routine vaccination would avert 90% of the disease burden and cost $498 million (16% savings compared with no vaccination) while outbreak vaccination would avert 67% of the disease burden and cost $552 million (6% savings). Both strategies were more costly than no vaccination from the healthcare payer perspective. Routine vaccination was cost-saving for all outcomes assessed from a societal perspective. Outbreak vaccination was cost-saving for averted symptomatic cases but cost from $5 [95% CI: cost savings, $191] per chronic joint pain case averted to $373,054 [95% CI: $172,643, $573,464] per death averted.